Workplace Relations, Skills-Training and Technological Change at Plant-Level - Campbell, Adrian; Warner, Malcolm (Relations industrielles / Industrial Relations, 1988)
This paper critically looks at workplace relations, skills training and technological change and asks whether they are necessarily linked together in an inflexible way, particularly where microelectronics applications are concerned. It then goes on to argue that 'automation' can lead to the re-assembly of skills where mass-markets become differentiated at saturated levels of demand, with important implications for training-strategies.